PENGARUH DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA PERAWAT RUMAH SAKIT IBU DAN ANAK ERIA PEKANBARU - Aisyah "; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine the effect of work discipline and job satisfaction on the performance of nurses at Eria Pekanbaru Mother and Child Hospital. In this study, the method used was a quantitative approach and used analytical tools, namely SPSS version 23. The respondents in this study were nurses at the Eria Pekanbaru Mother and Child Hospital as many as 76 people. Furthermore, the results obtained are that there is a positive and significant influence between Work Discipline (X1) and employee performance (Y), Job Satisfaction (X2) has a positive and significant effect on Employee Performance (Y), as well as Work Discipline (X1) and Job Satisfaction (X2) has a positive and significant effect on Employee Performance (Y) Eria other and Child Hospital Pekanbaru. Keywords: Work Discipline, and Job Satisfaction on Employee Performance